Behavior Disorders and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
A longitudinal study of 127 children with epilepsy aged 8-12 years and their mothers, designed to identify factors contributing to behavior problems, is reported from the Indiana University School of Nursing, Indianapolis; the Minnesota Comprehensive Epilepsy Program, Minneapolis; and the Harvard School of Public Health, Boston.